Life cycle and economic assessment of physical hydrogen storage tanks: Comparative analysis from steel to composite systems - Altuntas-Vahapo, Merve; Erdemir, Dogan (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
This study presents a detailed life cycle assessment and economic comparisons for the tanks that are used for storing hydrogen in various states: compressed gas (Type I-V, 100-1000 bar) and liquid (1-10 bar). A comprehensive model is created based on thermodynamic properties and tank geometries, which considers pressure-dependent material compositions to quantify cradle-to-gate emissions and material costs. The functional unit is selected to be 1 kg of stored hydrogen. The results demonstrate that type I tanks (steel), despite being the heaviest, have the least environmental impact and the lowest cost, with emissions of approximately 82-143 kgCO2e/kg H2, and costs ranging from $81 to $189/kg H2. Advanced composite tanks (type II-V) are subject to higher environmental and economic penalties because of the very high energy density of carbon fiber production (24.83 kgCO2e/kg H2). The emissions from composite tanks increase rapidly with increasing pressure; for a Type V tank at 1000 bar, the emissions are as high as 894 kgCO2e/kg H2, with costs exceeding $600/kg H2. Liquid hydrogen tanks have the best volumetric density, which falls between the environmental (180-276 kgCO2e/kg H2) and economic ($120-174/kg H2) ranges. Consequently, while high-pressure composite tanks reduce weight, they significantly increase both carbon footprint and cost. When space is not a limiting factor, Type I steel tanks remain the most cost-effective and environmentally preferable solution for stationary applications. Composite and liquid hydrogen tanks will be important for mobile applications and hydrogen transportation due to transportation emissions. However, there is a need to reduce emissions in both composite material manufacturing and tank production.
Keywords: Hydrogen; Hydrogen storage; Life cycle assessment; Economic assessment; Environmental impacts; Liquid hydrogen; Compressed-gas hydrogen; Chemistry; Electrochemistry; Energy & Fuels